Malaysian Library and Information Science Periodicals: A Historical Overview - Tiew, W.S. (Perpustakaan Negara Malaysia, 2001)
This article attempts to identify and compile a list of the earliest Malaysian LIS periodicals. The study found that the first professional LIS periodical published in Malaysia is Malayan Library Journal issued in October 1960 by the Library Association of the Federation of Malaya and the Library Association of Singapore. On the whole, between 1960 till the present, as many as ten Malaysian LIS periodicals were published by various library-related institutions, association and individual. Some of these publications are dormant, some ceased issuing their periodicals while others are still active coming out with their latest issue.